Analisis Retorika Dakwah Digital Ustadz Abu Bassam Oemar Mita dalam Teori Retorika Aristoteles - Arifin, Amalia Azka (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2023)
This study analyzes the digital da'wah rhetoric used by Ustadz Abu Bassam Oemar Mita through Aristotle's classical rhetoric theory approach, which consists of three main elements: ethos (credibility), pathos (emotion), and logos (logic). This study found that Ustadz Oemar Mita's ethos is built through a strong scientific background, consistency of preaching, and a simple lifestyle. The pathos aspect is evident in his ability to evoke the audience's emotions through a rhetorical language style, real-life examples, and expressive intonation. Meanwhile, his logos can be seen from the systematic use of arguments, contextual reasoning, and logical and easy-to understand arguments. Keywords : Digital preaching, Aristotle's rhetoric, ethos, pathos, logos, Ustadz Oemar Mita.